2020
DOI: 10.1146/annurev-psych-010419-051112
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory Integration as a Window into Orderly and Disrupted Cognition and Communication

Abstract: During our everyday lives, we are confronted with a vast amount of information from several sensory modalities. This multisensory information needs to be appropriately integrated for us to effectively engage with and learn from our world. Research carried out over the last half century has provided new insights into the way such multisensory processing improves human performance and perception; the neurophysiological foundations of multisensory function; the time course for its development; how multisensory ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 199 publications
3
69
0
Order By: Relevance
“…that specify the timescale over which radial and angular velocity are integrated. This 'leaky integration' model was refuted for neurotypical individuals by Lakshminarasimhan et al, 2018, but has been included here to compare between ASD and controls, given that one of the many ASD hypotheses claims deficient integration in this conditions (Iarocci & McDonald, 2006;Stevenson et al, 2014;Wallace et al, 2019).…”
Section: Path Integration Improves With Feedback Due To a Reduction Imentioning
confidence: 99%
“…that specify the timescale over which radial and angular velocity are integrated. This 'leaky integration' model was refuted for neurotypical individuals by Lakshminarasimhan et al, 2018, but has been included here to compare between ASD and controls, given that one of the many ASD hypotheses claims deficient integration in this conditions (Iarocci & McDonald, 2006;Stevenson et al, 2014;Wallace et al, 2019).…”
Section: Path Integration Improves With Feedback Due To a Reduction Imentioning
confidence: 99%
“…The literature on temporal order judgments involving sensory events is sizable and complex [4,57]. We make no claims to have simplified those complexities, nor was that our intention.…”
Section: Discussionmentioning
confidence: 96%
“…Importantly, studies have now specifically demonstrated relationships between multisensory temporal processing and severity of social and language impairments in individuals with ASD [Feldman et al, 2018; Patten, Watson, & Baranek, 2014; Stevenson et al, 2018; Wallace, Woynaroski, & Stevenson, 2020; Woynaroski et al, 2013]. Collectively, the body of evidence points to altered multisensory temporal function in ASD, and these temporal alterations are likely to have cascading effects on higher‐order social communicative skills that necessitate the rapid and accurate integration of multisensory information [Stevenson et al, 2016, 2018; Yaguchi & Hidaka, 2018; Zhou et al, 2018].…”
Section: Atypical Multisensory Processing In Autism Spectrum Disordermentioning
confidence: 99%
“…Indeed, if multisensory integration is a key building block in the construction of higher‐order cognitive representations, it may serve as a tractable target for intervention that would have benefits that have cascading impact across both the processing hierarchy as well as in development [Baum et al, 2015a; Robertson & Baron‐Cohen, 2017; Stevenson et al, 2018; Stevenson, Siemann, Schneider, et al, 2014; Thye et al, 2018]. With this possibility, it is important to carefully evaluate the potential relationships between multisensory processing and clinical domains such as social communication in ASD [Cascio, Woynaroski, Baranek, & Wallace, 2016; Feldman et al, 2018; Martínez et al, 2019; Patten, Labban, Casenhiser, & Cotton, 2016; Sartorato, Przybylowski, & Sarko, 2017; Wallace et al, 2020; Yaguchi & Hidaka, 2018].…”
Section: Translational Approaches For Asd: Relationships Between Multmentioning
confidence: 99%